Clinical applications of MARSALA for preimplantation genetic diagnosis of spinal muscular atrophy. (20th September 2016) - Ren, Yixin; Zhi, Xu; Zhu, Xiaohui; Huang, Jin; Lian, Ying; Li, Rong; Jin, Hongyan; Zhang, Yan; Zhang, Wenxin; Nie, Yanli; Wei, Yuan; Liu, Zhaohui; et al.
Abstract: Conventional PCR methods combined with linkage analysis based on short tandem repeats (STRs) or Karyomapping with single nucleotide polymorphism (SNP) arrays, have been applied to preimplantation genetic diagnosis (PGD) for spinal muscular atrophy (SMA), an autosome recessive disorder. However, it has limitations in SMA diagnosis by Karyomapping, and these methods are unable to distinguish wild-type embryos with carriers effectively. Mutated allele revealed by sequencing with aneuploidy and linkage analyses (MARSALA) is a new method allowing embryo selection by a one-step next-generation sequencing (NGS) procedure, which has been applied in PGD for both autosome dominant and X-linked diseases in our group previously. In this study, we carried out PGD based on MARSALA for two carrier families with SMA affected children. As a result, one of the couples has given birth to a healthy baby free of mutations in SMA-causing gene. It is the first time that MARSALA was applied to PGD for SMA, and we can distinguish the embryos with heterozygous deletion (carriers) from the wild-type (normal) ones accurately through this NGS-based method. In addition, direct mutation detection allows us to identify the affected embryos (homozygous deletion), which can be regarded as probands for linkage analysis, in case that the affected family member is absent. In the future, the NGS-based MARSALA method is expected to be used in PGD for all monogenetic disorders with known pathogenic gene mutation.